O programa Escola Viva no município de Alegre: o desenvolvimento do trabalho docente a partir da perspectiva dos professores - Gonçalves, Bianca (2019)
The present work is understood in the field of Basic Education and has as its object of study the Program of State High Schools in Single Turn , popularly known as Escola Viva Program, implemented by the state of Espírito Santo in 2015. The main object